Thermal Performance of Public Green Space using Palm Fiber Net-Based Green Canopy and Passion Fruit (Passiflora Edulis) Vegetation - Muksin, Engelina; Jahja, Mohamad; Setiawan, Dewa Gede Eka; Ramadani, A Indra Wulan Sari; Djafar, Abdi Gunawan; Latief, Muh. Fachrul (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2025)
This study aims to evaluate the thermal performance of green canopies in public green spaces (RTH), both outdoors and indoors, as an environmentally friendly solution. The method involved measuring temperature and humidity over a five-month period with four observation intervals. The data were analyzed using the Temperature-Humidity Index (THI) and compared with thermal comfort standards based on the Indonesian National Standard (SNI). The results show that at 0% plant coverage, the THI values fall into the